Upaya Pelestarian Kearifan Lokal Melalui Pengembangan Buku Peserta Didik Bertema IPA - Berti Yolida; Rini Rita T. Marpaung; Tri Jalmo; Ismi Rakhmawati (Universitas Lampung, 2018)
The research was intended to provide an overview of the actual conditions of local wisdom in the West Coast, then inserted to the books of learners. The design used in this research was simple descriptive. Data collecting technique using triagulation that was questionnaire to obtain the attractiveness books from 31 students, interviews of community leaders in West Coast about repong damar, interview of IV grade teachers about implementation of local wisdom in school, literature search about broad repong damar and field notes to obtain supporting information in the field. Data were analyzed using qualitative descriptive technique. The overall exposure sourced from the data obtained describe the local wisdom and the importance of preservation efforts of local wisdom in West Coast. The results of the book's attractiveness test criteria was 97.1%